VD_FINDINFO HC / 2020 / 494 vom 19. August 2020 - VD Tribunal cantonal (2020)
LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE, DOMMAGE, PERTE DE GAIN, TORT MORAL | 42 al. 2 CO, 46 CO, 47 CO, 92 al. 1 CPC, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 404 al. 1 CPC (CH)